Employable graduate: UiTM professional accountancy program experience / Nooraslinda Abdul Aris and Mira Susanti Amirrudin - Abdul Aris, Nooraslinda; Amirrudin, Mira Susanti (2023)
Higher Learning Institutions (HLIs) should aim to produce high-quality human capital that meets local demand and is globally marketable. HLIs need to take stock of the current state of graduate employability from both the employers' and the graduates' perspectives if they are to respond effectively to the knowledge and skills requirements of the industry. Globally, graduate employability is a concept that is becoming increasingly popular in the higher education sector. The underlying assumption is that graduates need attributes other than those skills needed in the subject-specific discipline. This article provides a sharing experience of the professional accountancy program in UiTM, especially on the journey of getting the platinum status awarded by the global professional accounting body. In addition, two key points worth sharing are the student's top achievement and how to be employable once they complete their study.